(3YbjOI Cgd GdSfIs - (3YHO Gddg Hf CMeO Hf eMeO Hf bOGeI GdLeGYjdj GdebOSj Ke GdOeTbj GdMfHdj, ehab GdOjf GHf bOGeI , J (B620 (3gs
(3ChdgG (B:s
(3bGd GdTjN CHh eMeO YHO Gddg Hf CMeO Hf eMeO Hf bOGeg GdebOSi GdMeO ddg GdeMehO Hcd dSGf GdeYHhO ai cd ReGf GdPi dGjNdh ef Ydeg ecGf hbGd GdEeGe CHh YHO Gddg CMeO Hf MfHd ai bhd GdfHi Udi Gddg Ydjg hSde (B( (3jfRd Gddg YR hLd Edi SeGA GdOfjs
(3BNQgG (B:s
(3aEf GdENJdGa ai GdaQhY QMeI hGdeMOKjf ajg eMehOjf ai ENJdGage eKGHhf ai ELJgGOge hENJdGage QMeI hGSYI hEJaGbge MLI bGWYI hGdMeO ddg hMOg s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B67 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B30 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B459s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdHOjQi HGdbOS s
Keywords: (3GNJdGa GdabgGAs